Phenoxazine Radical as a Positive Material for Neutral pH Aqueous Flow Batteries - Martínez-González, Eduardo; Tuna, Ali; Peljo, Pekka (American Chemical Society, 2025)
Understanding electron transfer reactions in phenoxazine aqueous-soluble electroactive materials is crucial for developing flow battery (FB) electrolytes, especially for the positive side. Here, we prepared a water-soluble phenoxazine methyl celestine blue compound (mCB) to demonstrate its relatively high redox potential and study its reversible redox chemistry in aqueous KCl solutions. This flow battery (FB) electrolyte exhibited full capacity retention when tested in a symmetrical cell operated at 86% capacity during 55 charge–discharge cycles. The stability of the radical species formed during the one-electron reduction process of mCB (to obtain the positive electrolyte of the FB cell) was also characterized by cyclic voltammetry and electron paramagnetic resonance (EPR) spectroscopy. This electrolyte was also tested against a viologen-based negolyte, and the detected capacity loss (after 55 cycles) was related to a degradation mechanism of the mCB compound undergoing proton oxidation reactions. The experimental results suggest that a more exhaustive characterization by cyclic voltammetry be considered when analyzing FB electrolytes, in order to also take into account the possible effect of inner-sphere electron transfer reactions on the reaction mechanism and its electrochemical parameters.